Peace Education for Sustainable Peace and Development: A Case of Kenya - Maiyo, Julius, K.; Ngao, Gladys; Mulwa, David M.; Mugambi, Paul (Journal of Research in Peace, Gender and Development, 2012)
A culture of peace will be achieved when citizens of the world understand global problems; have the skills to resolve conflicts constructively, know and live by international standards of human rights, gender and racial equality, appreciate cultural diversity and respect the integrity of the Earth. Such learning cannot be achieved without intentional, sustained and systematic education for peace. Education is the single most important means for empowerment and sustained improvement in all well being. Sustainable development is a basic Human Right and unless this target is reached with the potent tool of Education the purpose of Education would remain unfulfilled. Building a culture of peace and learning to live together is the responsibility of everyone, and education is the principal means by which this goal can be achieved. For this to become reality, nations must develop social-emotional and ethical values, attitudes and skills that sustain social coexistence in which everyone participates, shares and develops fully. Africa as continent has featured continuously in the world news due to frequent conflict and violence where several lives and properties have been destroyed, most recent is Sudan, Congo, Zimbabwe Kenya, Ivory Coast and Egypt among others. The present paper articulates peace education as the soul of education that can create the shield for human survival and development, discussed also is the role of teachers in peace education. The study concludes that Peace education is an essential component of quality basic education in Kenya, Economic and social development is linked with peace and cannot be achieved in a country where there is violence and social instability. Peace Education is thus urgently needed as a way of finding new solutions and improving the living conditions of millions of people. The study recommends that government should promote the training of Teachers and Administrators towards peace education and democratic interactions
Keywords: Peace education; Peace; Sustainable development